Recurrence of pituitary adenomas after transcranial operation. Issue 9 (September 1982) - Symon, L; Logue, V; Mohanty, S
Abstract : A series of 289 pituitary adenomas operated upon transcranially have been assessed for the frequency of recurrence. Ten patients died in the postoperative period, and nine patients have been lost to follow up. Follow up data is therefore available in a series of 270 cases for a period extending up to 30 years after the initial operation. There have been 13 histologically verified recurrences (4.8%), and a further six cases are known from CT scan or air study evidence to have residual or recurrent tumour which has not necessitated re-exploration. The total recurrence or residual tumour rate could therefore be regarded as 7.4%. The large majority (77%) of recurrences have been within 10 years of the first operation, and the rest between 10 and 20 years. Histologically, all were chromophobe adenomas, and the average age of their initial presentation was lower than the peak incidence of pituitary adenoma as a whole. Two patients showed frank malignant change in the second biopsy. In recurrent tumours, most had had only subtotal excision with some macroscopic evidence of invasion or degeneration, such as cystic change, haemorrhage or necrosis. Microscopic evidence of aggressive growth and capsular invasion by tumour cells also was relatively frequent. Postoperative radiotherapy decreased and delayed recurrence, although the vast majority of cases in the series received radiotherapy. Surgery for recurrence appeared an effective method of treatment, and no patient died following repeated operation. Initial transcranial excision in more recent years using the operating microscope followed by uniform radiotherapy, appears to have considerably reduced the already small recurrence rate of pituitary adenoma.